DIFFERENCES IN LED VALUES IN DENGUE FEVER PATIENTS WITH HEMOCONCENTRATION AND NOT HEMOCONCENTRATION - Rismita Pritanti (2019)
Background: Patients with dengue fever with hemoconcentration will experience plasma tearing (loss of plasma protein) which will affect the value of the Erythrocyte Sedimentation Rate (LED). Plasma proteins that play a role in influencing the value of the Sedimentation Rate (LED) are fibrinogen and globulins. An erythrocyte sedimentation (LED) examination measures the degree of erythrocyte deposition in a blood sample over a period of time. LEDs are sensitive but not specific tests. Purpose: To determine the difference in LED values of DHF patients with hemoconcentration and not hemoconcentration. Methods: Observational analytic, 30 samples with criteria for dengue fever patients with hemoconcentration and not hemoconcentration were examined at the Clinical Pathology Laboratory of Haji Hospital Surabaya in March - April 2019. The study used an independent t test with SPSS 16.0 program to determine whether there were differences in LED values in dengue fever patients with hemoconcentration and not hemoconsetration. Results: The results of the Independent t test showed that there were significant differences between the results of the erythrocyte sedimentation rate in patients with dengue fever with hemoconcentration and not hemoconsetration with Sig. (2-failed) of 0.00 (p <0.005). Conclusion: There are significant differences in sediment rate results with the Westergreen blood method in patients with dengue fever who experience hemoconcentration and who do not experience hemoconcentration.